Analysis of the Genomic Sequence of ABO Allele Using Next-Generation Sequencing Method - He, Yanmin; Hong, Xiaozhen; Zhang, Jingjing; He, Ji; Zhu, Faming; Huang, He (Frontiers in Immunology, 2022)
Background Although many molecular diagnosis methods have been used for ABO genotyping, there are few reports on the full-length genomic sequence analysis of the ABO gene. Recently, next-generation sequencing (NGS) has been shown to provide fast and high-throughput results and is widely used in the clinical laboratory. Here, we established an NGS method for analyzing the sequence of the start codon to the stop codon in the ABO gene. Study design and methods Two pairs of primers covering the partial 5'-untranslated region (UTR) to 3'-UTR of the ABO gene were designed. The sequences covering from the start codon to the stop codon of the ABO gene were amplified using these primers, and an NGS method based on the overlap amplicon was developed. A total of 110 individuals, including 88 blood donors with normal phenotypes and 22 ABO subtypes, were recruited and analyzed. All these specimens were first detected by serological tests and then determined by polymerase chain reaction sequence-based typing (PCR-SBT) and NGS. The sequences, including all the intron regions for the specimens, were analyzed by bioinformatics software. Results Among the 88 blood donors with a normal phenotype, 48 homozygous individuals, 39 heterozygous individuals and one individual with a novel O allele were found according to the results of the PCR-SBT method. Some single-nucleotide variants (SNV) in intronic regions were found to be specific for different ABO alleles from 48 homozygous individuals using the NGS method. Sequences in the coding region of all specimens using the NGS method were the same as those of the PCR-SBT method. Three intronic SNVs were found to be associated with the ABO subtypes, including one novel intronic SNV (c.28+5956T>A). Moreover, six specimens were found to exhibit DNA recombination. Conclusion An NGS method was established to analyze the sequence from the start codon to the stop codon of the ABO gene. Two novel ABO alleles were identified, and DNA recombination was found to exist in the ABO alleles.